The national question and the question of crisis - Zarembka, Paul (Emerald, 2010)
This volume focuses on nationality's efficacy in much of world affairs, and on the background and current issues surrounding global crisis. As one of the most famous Marxist revolutionaries, Rosa Luxemburg vigorously promoted her own conceptions, often opposing Lenin, her contemporary. In this volume, Narihiko Ito offers a much needed, extensive analysis of her position. This is followed by a critique of the current Iranian conjuncture, offered by Farhang Morady. The development of crises in capitalism is addressed both directly and indirectly within the volume. Alan Freeman argues the need to extricate French positivism from the Marxism that developed after Marx whilstRadhika Desai highlights renewed consideration of the major role of consumption demand in Marxist theory and considers implications for the current crisis. The volume continues with Karen Petersens analysis of the post-WWII developments of major currencies and Fabien Tarrit considers capitalism as an inherently unstable system, requiring a focus on its rate of profit. The final chapter by Jorgen Sandemose presents a careful argument offering notions of the origins of Marxs Capital culminating in an engaging volume that addresses The National Question and the Question of Crisis.
Keywords: Political Science -- Economic Conditions.; Philosophy -- Political.; Political Science -- General.; Marxism & Communism.; Political economy.; Financial crises.; Economics.; elektronické knihy; electronic books